A categoria Estado na obra de Milton Santos - Vicensio, João Paulo (2011)
The State, through / by material and human resources that make use of, is undoubtedly the most responsible (through action or omission) for changes in geographic space, which concern not only to geographers (a nature curious when the subject is space), but also all that are anyway affected by the changes. The topic of this research is the connecting / linking between State & Area and how it became a geographic speech. To make it possible, only the geographer Milton Santos was chosen to be analysed, in order to demonstrate how this major author of brazilian Geography realized this dependence becoming the State one of the most important categories of their studies